Efektivitas Fungsi Pengawasan DPRD terhadap Pelaksanaan APBD Kota Parepare - Ariady, Achmad; Ariadin (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2026)
This study aims to analyze the effectiveness of the supervisory function of the Regional House of Representatives (DPRD) over the implementation of the Regional Revenue and Expenditure Budget (APBD) and to identify the factors influencing it in Parepare City. This research employs an empirical method with a qualitative approach, conducted at the DPRD Office of Parepare City, South Sulawesi Province. Data were collected through interviews and analyzed using a descriptive-analytical technique. The findings reveal that the effectiveness of the DPRD’s supervisory function over APBD implementation has not been optimal, despite its strategic role in promoting accountable and transparent governance. This ineffectiveness is influenced by several interrelated factors, including inadequately operational legal substance, institutional structures that do not fully support the principle of checks and balances, a predominantly transactional legal culture, limited legal and technical budgetary knowledge among DPRD members, and insufficient supporting facilities and infrastructure. These findings highlight a gap between the normative framework and empirical practice in the implementation of DPRD’s supervisory function at the regional level.